Exploitation Drives Changes in the Population Connectivity of Queen Conch (Aliger gigas) - Vaz, Ana C.; Karnauskas, Mandy; Paris, Claire B.; Doerr, Jennifer C.; Hill, Ronald L.; Horn, Calusa; Miller, Margaret H.; Neuman, Melissa; McCarthy, Kevin J.; Farmer, Nicholas A. (Frontiers in Marine Science, 2022)
The queen conch, Aliger gigas, is an endemic and iconic marine gastropod of the Wider Caribbean region that has been harvested for thousands of years. Conch are slow-moving and require contact to mate; overfishing has reduced populations in many areas compromising its rates of reproduction. Long-range dispersal and mixing between distinct populations occur in the queen conch’s early life history stages, when pelagic larvae are transported by oceanic currents. Genetic studies suggest that gene flow between populations decreases as the distance between populations increases. Here, we assessed how the population connectivity of conch changes with spatially variable patterns of fishing exploitation by simulating larval dispersal and comparing the potential connectivity under an unexploited and a contemporary exploited reproductive scenario. Results demonstrate that reduced egg production, due to heterogeneous fishing pressure and localized depletion, significantly alters population connectivity patterns as well as the structuring of populations and metapopulations across the species’ range. This strongly suggests that estimates of contemporary demographic rates, together with estimates of reproductive output need to be included in population connectivity studies. The existence of self-sustained metapopulations of queen conch throughout the Wider Caribbean suggests that replenishment through larval dispersal occurs primarily within sub-regional spatial scales, emphasizing the need for regional and local conservation and management measures to build and protect reproductively active populations and nursery habitat across multiple jurisdictions.